Rapid variations in fluid chemistry constrain hydrothermal phase separation at the Main Endeavour Field. (7th February 2017) - Love, Brooke; Lilley, Marvin; Butterfield, David; Olson, Eric; Larson, Benjamin
Abstract: Previous work at the Main Endeavour Field (MEF) has shown that chloride concentration in high‐temperature vent fluids has not exceeded 510 mmol/kg (94% of seawater), which is consistent with brine condensation and loss at depth, followed by upward flow of a vapor phase toward the seafloor. Magmatic and seismic events have been shown to affect fluid temperature and composition and these effects help narrow the possibilities for sub‐surface processes. However, chloride‐temperature data alone are insufficient to determine details of phase separation in the upflow zone. Here we use variation in chloride and gas content in a set of fluid samples collected over several days from one sulfide chimney structure in the MEF to constrain processes of mixing and phase separation. The combination of gas (primarily magmatic CO2 and seawater‐derived Ar) and chloride data, indicate that neither variation in the amount of brine lost, nor mixing of the vapor phase produced at depth with variable quantities of (i) brine or (ii) altered gas rich seawater that has not undergone phase separation, can explain the co‐variation of gas and chloride content. The gas‐chloride data require additional phase separation of the ascending vapor‐like fluid. Mixing and gas partitioning calculations show that near‐critical temperature and pressure conditions can produce the fluid compositions observed at Sully vent as a vapor‐liquid conjugate pair or as vapor‐liquid pair with some remixing, and that the gas partition coefficients implied agree with theoretically predicted values. Plain Language Summary: When the chemistry of fluids from deep sea hot springs changes over a short time span, it allows us to narrow down the conditions and processes that created those fluids. This gives us a better idea what is happening under the seafloor where the water is interacting with hot rocks and minerals, boiling, and taking on the character it will have when it emerges at the seafloor. Gasses like argon can be especially helpful here. We found that the fluids we sampled must have been formed by multiple boiling (phase separation) events, and that one of these would have to be close to the critical point of these fluids. Key Points: High frequency sampling captured an excursion in fluid chemistry, clarifying constraints on phase separation and mixing processes. The most likely explanations include brine condensation at depth followed by near‐critical phase separation and mixing. Multidimensional data sets including gasses help interpret variability in records of temperature and salinity in hydrothermal systems.